Regional variations of the impact of role models and fear of failure on entrepreneurship amongst the youth (2017)
This paper examines the joint influence of two individual level factors on entrepreneurship amongst youth residing in the rural regions. Using data from an adult population survey (APS), our empirical results suggest that although the youth in rural regions are equally likely to be positively influenced by entrepreneurial role models, rural youths are more likely to refrain from entrepreneurship because of the greater level of fear of failure compared to urabn youths. We suggest ways how by understanding differences in the influence of entrepreneurial role models and fear of business failure policy makers can design locally relevant entrepreneurship policies. By using a more fine grained analysis in the form of the moderating effect of two important individual level factors, our study contributes to a better understanding of the barriers to entrepreneurship in lagging (rural) regions at the country level